PENGARUH PEMBELAJARAN BERBASIS EKSPERIMEN, PEMBELAJARAN BERBASIS OBSERVASI DAN PEMBELAJARAN BERBASIS INTERPRETASI DALAM PROGRAM SAINS CLUB TERHADAP PENINGKATAN PRESTASI BELAJAR SISWA PADA SEKOLAH MITRA SAINS CLUB KOTA TANGERANG - Imam Sujito; Sri Utaminingsih; Dani Rahman Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of experiment-based learning, observation-based learning, and interpretation-based learning in the Science Club Program on improving students' academic achievement at Science Club Partner Schools in Tangerang City. The study employed a quantitative method with a causal associative approach to examine the relationships and effects of the independent variables on the dependent variable. The research population consisted of 75 teachers from Science Club Indonesia Partner Schools, with a sample of 63 respondents determined using the Slovin formula at a 5% margin of error. The sampling technique used was proportional stratified random sampling, followed by simple random sampling within each school cluster. Data were collected using a Likert-scale questionnaire that had met the requirements of validity and reliability. Data analysis was conducted using descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results indicate that experiment-based learning, observation-based learning, and interpretation-based learning each have a positive relationship with the improvement of students' academic achievement. Furthermore, the combinations of experiment-based learning and observation-based learning, experiment-based learning and interpretation-based learning, as well as observation-based learning and interpretation-based learning also demonstrate positive relationships with students' academic achievement. Simultaneously, experiment-based learning, observation-based learning, and interpretation-based learning within the Science Club Program have a positive effect on improving students' academic achievement. The findings suggest that the integrated implementation of these three learning approaches creates a more active learning experience, enhances students' scientific thinking skills, and contributes to improved academic achievement.